Three-dimensional measurement and cohesive element modelling of deformation and damage in a 2.5-dimensional woven Ceramic Matrix Composite - Saucedo Mora, L; Zou, C; Lowe, T; Marrow, T (Wiley, 2016)
A cohesive element numerical model, which reproduces the three-dimensional microstructure of a 2.5-dimensional Silicon-Nitrogen-Oxide fibre/fabric reinforced Boron Nitride ceramic matrix composite (SiNO/BN) is applied to simulate the failure of specimens that are observed in situ during diametral compression testing. Measurements of deformation by image correlation of 2-dimensional optical surface observations and 3-dimensional X-ray computed tomographs are used to fit the simulation’s elastic properties for the matrix and fibre tows. The observed patterns of damage nucleation and propagation are correctly simulated using a local tensile strain criterion.